Midlife Physical Activity Preserves Lower Extremity Function in Older Adults: Age Gene/Environment Susceptibility–Reykjavik Study. Issue 2 (15th January 2013) - Chang, Milan; Saczynski, Jane S.; Snaedal, Jon; Bjornsson, Sigurbjorn; Einarsson, Bjorn; Garcia, Melissa; Aspelund, Thor; Siggeirsdottir, Kristine; Gudnason, Vilmundur; Launer, Lenore J.; Harris, Tamara B.; Jonsson, Palmi V.
<x xml:space="preserve">Abstract</x> Objectives To examine the long‐term association between midlife physical activity (PA) and lower extremity function (LEF) in late life. Design Longitudinal study with an average of 25 years of follow‐up. Setting Community‐dwelling old population in Reykjavik, Iceland. Participants Four thousand seven hundred fifty‐three community‐dwelling men and women (mean age 76 ± 6) in Reykjavik, Iceland. Measurements On the basis of weekly hours of regular PA reported at the midlife examination, participants were classified as active or inactive. Measures of LEF in late life were gait speed on a 6‐m walk, Timed Up and Go (TUG), and knee extension (KE) strength tests. Linear regression analysis was used to examine the association. Results Participants who were active in midlife had significantly better LEF (faster gait speed, β = 0.50, P ≤ .001; faster TUG time, β = –0.53 P ≤ .001; stronger KE strength, β = 1.3, P ≤ .001) in late life than those who were not active in midlife after adjusting for sociodemographic and cardiovascular risk factors. After adjustment for cognitive function in late life (speed of processing, memory, and executive function), participants who were active in midlife had significantly faster gait speed (β = 0.04, P ≤ .001), faster TUG time (β = −0.34, P ≤ .001), and greater KE strength (β = 0.87, P ≤ .001) in old age than those who were not active in midlife. Conclusion Regular PA in midlife is associated with better performance of LEF in later life, even after controlling for late‐life cognitive function.